HISTORICAL AND PHILOSOPHICAL ANALYSYS OF SOCIAL DEVELOPMENT (Archive of Conferences, 2021)
The article deals with the issue on social development. There are discussed the two groups of social development theories: spiritual and materialistic ones. The author identifies the problem of the humankind progress and shares his view concerning its sense.